Vanashree: A promising improved purebred native chicken for free-range or backyard farming - Haunshi, Santosh; U, Rajkumar; K, Padhi M; M, Niranjan; L, Prince L L; N, Chatterjee R (Indian Farming, 2022)
Improvement of production performance of native chickens is essential for increasing the productivity of backyard or free-range systems of poultry. Vanashree, an improved indigenous chicken was evolved from Aseel-Peela (PD-4) breed through selective breeding for improvement of body weight and egg production. They have a majestic look with attractive yellow coloured plumage, yellow shanks and red pea combs. Vanashree hens produce eggs with brown to light brown coloured shells. The appearance of eggs is similar to those of any other native chickens. Hens show broodiness behaviour under field conditions. The average fertility and hatchability (Fertile eggs set) observed over the last 11 generations was 81 and 79%, respectively. The dressing percentage observed in male and females was 68.6% at 20 weeks of age and the abdominal fat percentage was 0.39%. This bird has the lean meat, and flavour and texture of native chickens. Vanashree birds are attractive, hardy and aggressive in nature. They are suitable as a dual-purpose bird for meat and egg production under free-range, backyard and semi-intensive systems of production.